Penguatan Literasi sebagai upaya preventif terhadap Radikalisme-Ekstremisme Beragama di Pondok Pesantren Assalaam Manado - Abdullah Botma; Abdurrahman Wahid Abdullah (IAIN Manado, 2022)
Strengthening Literacy as a preventive effort against Radicalism-Religious Extremism at the Assalaam Islamic Boarding School Manado. The spread of extremist ideologies is often linked to religious institutions, including madrasahs and boarding houses. Its message has long been known as a moderate, tolerant religious institution known as